Seventh Five Year Plan 1985-90 Draft Annual Plan 1986-87 Part-II Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1985)
It is proposed to bring 8000 hect. of land out of the total available area of 12000 hect. of paddy land under H.Y.V. and the remaining area under other improved varieties by the end of the seventh plan. Area under double cropping.
Andaman and Nicobar Administration
Andaman and Nicobar Administration